THE EFFECTIVENESS OF INTERACTIVE FLAT PANEL (IFP) UTILIZATION IN SUPPORTING INNOVATIVE IPAS LEARNING IN ELEMENTARY SCHOOLS - Okto Naitboho; Rey Naldo; Elisabeth Ruth Deku; Restiana Embong Bulan; Maria Elfira Bumbung; Seprisidian Duka (Paradigma: Jurnal Filsafat, Sains, Teknologi, dan Sosial Budaya, 2025)
Educational transformation in the digital era has intensified the adoption of innovative learning technologies, one of which is the use of Interactive Flat Panels (IFPs) in elementary education. This study aims to examine the effectiveness of IFP utilization in fostering instructional innovation in Natural and Social Sciences (Ilmu Pengetahuan Alam dan Sosial—IPAS) at elementary schools in Kupang City, as well as to explore the factors influencing its implementation within the local socio-cultural context. Employing a qualitative approach with a descriptive case study design, data were collected through semi-structured interviews, participatory observations, and document analysis involving teachers, school principals, and students from three elementary schools that received IFP support. Data analysis was conducted using Miles and Huberman’s interactive model complemented by thematic analysis. The findings indicate that the use of IFPs has enhanced students’ interest and engagement in IPAS learning, particularly through material visualization and multimedia-based instruction. Nevertheless, their utilization remains partial and predominantly situated at the substitution level, thus falling short of fully supporting interactive and collaborative learning practices. Major constraints include teachers’ limited pedagogical and technological competencies, the lack of sustained professional development, as well as infrastructural limitations and school cultural barriers. This study underscores that the effectiveness of IFP implementation is determined not merely by technological availability, but also by human resource readiness, institutional support, and the integration of local values. The findings are expected to inform the development of more contextualized and sustainable digital learning policies and implementation strategies in elementary education.